The effects of subsidiary’s leadership and entrepreneurship on international marketing knowledge transfer and new product development - Crespo, Cátia Fernandes (2022)
This study investigates the role of a strong subsidiary leadership and entrepreneurial culture in the promotion of marketing knowledge inflows. We further examine their consequences on the subsidiary’s ability to develop new products when moderated by the tastiness of knowledge. The data were collected from 202 Portuguese subsidiaries of multinational corporations and were analyzed using partial least squares structural equation modelling to test the hypotheses. The results indicate that subsidiaries’ strong leadership support and entrepreneurial culture are fundamental mechanisms that foster marketing knowledge inflows from both the headquarters and peer subsidiaries. Moreover, marketing knowledge inflows enhance the focal subsidiary’s innovation abilities. We also find that tacit knowledge exerts contradictory moderating effects on the transfers of marketing knowledge, carrying distinct implications for a subsidiary’s knowledge management. The results expand our understanding of the effectiveness of transferring marketing knowledge among multinational corporations’ (MNCs) subsidiaries.